On-line survey: Women in IT-what their male colleagues think of them / Lim Lih Jen - Lim , Lih Jen (2004)
This project documentation is an exercise submitted to the Faculty Computer Science and Information Technology, University of Malaya, as a report for the Final Year Project Level One, WXES3181 and Final Year Project Level Two, WXES3181, which in turn serves as a partial fulfillment for the Bachelor of Information technology degree. The system proposed in Online Survey System, which will look into the perception of male to their female colleague in IT. The site providing the online questionnaire to the respondents. This system will show the result of the survey in graphical way such as bar chart. Online survey System is divided into two sections Administrator Section and Respondent Sections. Basically, Administrator section is also provided authority to edit the questionnaires and retrieve the data form database as analysis purpose. The respondents can answer the questionnaires and view the result of the survey. During the WXES3181, the scope will cover until system design chapter. The next stage WXES3181, during this stage; the thesis will cover system implementation, system testing and system evaluation and conclusion.